Serology Confirms Near-Absence of Malaria Transmission in Timor-Leste - Elfiana De Fatima Amaral; Isabel Byrne; Helena Brazal Monzo; Raul Sarmento; Maria Do Rosario De Fatima Mota; Gregorio Rangel; Maria Tanesi; Antonio Salles de Sousa; Nelson Martins; Tessa Oakley; Lucsendar Alves; Jennifer Yan; et al. (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Despite malaria remaining a major public health threat, several countries have made significant progress toward elimination. Timor-Leste has reduced the number of malaria cases from more than 200,000 to zero, with no indigenous cases reported since 2022, and has recently been certified as malaria-free by the WHO. At low transmission levels, serological surveys, which detect antibodies to malaria parasites, can augment conventional surveillance by revealing the absence of antibodies and, therefore, of exposure in previously endemic populations. Exposure to malaria, as determined using antibody responses to antigens from Plasmodium falciparum ( P. falciparum ) and Plasmodium vivax ( P. vivax ), was assessed in 4,631 participants recruited from all municipalities in Timor-Leste. These antigens are associated with recent and cumulative exposure to each species. Age-specific seroprevalence was assessed, and seroconversion was estimated using reverse catalytic models. Risk analysis for individual and geographical exposure was also conducted. Seroprevalence to recent exposure to P. falciparum antigens was uniformly low across age groups (1.4% [95% CI: 1%–2%]) and consistent with the absence of ongoing transmission. The recent seroprevalence of P. vivax was similarly low (0.2% [95% CI: 0.1%–0.3%]). The time of change in the force of infection was consistent with the country’s scale-up for elimination. Areas at lower altitudes and those with higher historical tree cover had evidence of the highest co-endemic historical exposure. The serological analysis supports passive and active surveillance malaria data in confirming the near-absence of ongoing transmission in Timor-Leste. In low-transmission settings, sero-epidemiological surveillance can provide key information on transmission that will benefit control programs.